2015
DOI: 10.1002/jcb.25294
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Overexpression Cooperates With Lithium to Reduce the Malignancy and to Increase Cell Death by Apoptosis via PI3K/Akt Suppression in Colorectal Cancer Cells

Abstract: Lithium is a well-established non-competitive inhibitor of glycogen synthase kinase-3β (GSK-3β), a kinase that is involved in several cellular processes related to cancer progression. GSK-3β is regulated upstream by PI3K/Akt, which is negatively modulated by PTEN. The role that lithium plays in cancer is controversial because lithium can activate or inhibit survival signaling pathways depending on the cell type. In this study, we analyzed the mechanisms by which lithium can modulate events related to colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
1
18
0
3
Order By: Relevance
“…The PTEN/PI3K/AKT pathway is highly involved in CRC progression [43, 44]. A previous report demonstrated that Sp1 can inhibit PTEN expression by binding to the PTEN promoter region [45].…”
Section: Discussionmentioning
confidence: 99%
“…The PTEN/PI3K/AKT pathway is highly involved in CRC progression [43, 44]. A previous report demonstrated that Sp1 can inhibit PTEN expression by binding to the PTEN promoter region [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that several signal transduction pathways can determine cell's fate under variety of stressful conditions 27. Among those signaling pathways, phosphoinositide 3-kinase (PI3K)/Akt is mainly involved in oxidative stress triggered cell death and is considered to deliver survival signals to protect cells from apoptosis 28. In the current study, we examined the marked increase of Akt phosphorylation when shock wave treatment beyond 100 impulses and if this treatment beyond 200 impulses the significant increase of phosphorylation of glycogen synthase kinase-3 (GSK-3β) can also be observed (Fig A-C).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a potent tumor suppressor and contributes to the regulation of cell survival, apoptosis, proliferation, metabolism, and migration through suppressing PI3K oncogenic pathway (de Araujo et al, 2016). Moreover, downregulation of PTEN, which is reported in nearly half of all cases, is associated with cancer progression in patients with HCC (Hu et al, 2003;Khalid, Hussain, Manzoor, Saalim, & Khaliq, 2017).…”
Section: Pi3k/akt Signaling Regulatory Oncogenic Mirnas In Hcc Pathmentioning
confidence: 99%